The Rhetoric of Chin P'ing Mei - Carlitz, Katherine (Indiana University Press, 1986)
Chin p'ing mei, the late Ming dynasty novel, combines rich sensuous detail with an interweaving of reality and fantasy to create a telling portrait of the dynasty's decline. In addition to the explicit sexual detail, the novel also contains a stern Confucian message about the retribution to be expected from decline. Professor Garlitz analyzes the author's varied techniques, the dominant concerns of late Ming China (such as the relationship between family and state, the individual's need for self-knowledge and self-cultivation), and the verbal and narrative structure. Where Chin p'ing mei draws on late Ming popular religion, or quotes drama and song, or incorporates portions of earlier novels and tales, the effect is always the same: hypocrisy and complacency are exposed, facile solutions to difficult moral problems are rejected, and traditional Confucian judgments are affirmed.